Highly efficient core–shell Ag@carbon dot modified TiO2 nanofibers for photocatalytic degradation of organic pollutants and their SERS monitoring. Issue 45 (16th July 2020) - Jin, Jing; Song, Wei; Zhang, Ning; Li, Linjia; Liu, Hao; Yang, Bai; Zhao, Bing
Abstract : The possible mechanism of enhanced photocatalytic performance of Ag@CDs–TiO2 hybrid NFs. Abstract : In the present study, a novel hybrid nanomaterial composed of core–shell structured Ag@carbon dot (CD) modified TiO2 nanofibers (NFs) was successfully fabricated via a simple two-step strategy for the first time. Herein, the Ag@CDs–TiO2 NFs are demonstrated to be an efficient SERS substrate. The strong LSPR-induced electromagnetic enhancement (EM) by Ag@CDs NPs and efficient charge transfer (CT) effect between Ag@CDs and TiO2 NFs synergistically contribute to the excellent SERS enhancement. In addition, the Ag@CDs–TiO2 NFs exhibit enhanced photocatalytic activity regarding the organic pollutant degradation under visible light irradiation because of the enhanced light absorption and improved separation of photo-generated electron–hole pairs. Thus, this new nanocomposite can be used as a sensitive SERS substrate for determining the catalytic activity and reaction kinetics during the photodegradation of methylene blue (MB). Compared with UV-vis spectroscopy, the SERS technique enables more accurate monitoring of the changes of adsorption molecules and actual catalytic process on the surface of the catalyst. These results are significant for the development of metal or semiconductor-based catalysts for ensuring optoelectronic, energy and environmental applications.